The effect tig welding parameters on mechanical properties of stainless 321 by Taguchi method (Comprehensive Journal of Science, 2025)
Welding is an area in which technological developments out match the developments in its science base which is primarily driven by the phenomenal industrial demand for welded structure. Taguchi s Design of experiment approach is used to study the effect of welding parameters on the mechanical properties of stainless steel 321. This research investigates the effects of welding current, gas flow rate and welding speeds at different ranges on the welding joints, hardness, and tensile behavior of austenitic stainless steel type 321. The factor used in this study consisted of welding current, gas flow rate and welding speed each of which had three levels. L9 orthogonal array were selected according to the aforementioned factor and levels and experimental tests were performed. Signal-to-noise (SN) ratio was used to evaluate the experimental result. , the as-received 321 austenitic stainless steel sheet was cut with shear cutting machine into sample of dimensions 350 mm length, 260 mm width and 2 mm thickness, Eighteen samples were produced, nine samples were defended in to group A, B and C respectively. The grouped samples were further cut into two equal halves with milling machine and welded using Tungsten Inert Gas Welding (TIGW) process. The obtained welded samples and as-received sample were machined to standard tensile test specimens, and tensile test was made using standard approaches.. The analysis of the variance (ANOVA), the best optimal levels and the effect of the process parameters on welding joints were obtained. In addition the optimum welding sample was number two which has maximum tensile strength of 462.87 N/mm2 and maximum hardness of 123 HB. this was obtained from welding current of 50A, welding speed of 6mm/sec and gas flow rate 30 l/.